Biochemical properties of red tilapia (Oreochromis niloticus) protein hydrolysates - Shamloo, M.; Bakar , Jamilah; Mat Hashim, D.; Khatib, Alfi (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
The amino-acid composition, 2, 2-Diphenyl-1-picryhydrazyl (DPPH) radical-scavenging activity, and peptide patterns of tilapia protein hydrolysates produced by the enzymatic hydrolysis of Alcalase (AH), Flavourzyme (FH) and Protamex (PH) for 5h using pH-stat method were studied. The ratio of essential amino acids to non-essential amino acids increased after hydrolysis in all samples; however, no significant differences among them were observed. AH had a highest (P < 0.05) DPPH radical-scavenging activity, but no significant difference in the DPPH between FH and PH was observed. SDS-PAGE patterns for all the hydrolysates showed significant (P < 0.05) reduction in the number and the intensity of the bands with increasing time of hydrolysis. Flavourzyme showed the lowest rate of hydrolytic activity towards the tilapia mince.